Relevansi Kurikulum PGMI Terhadap Capaian Pembelajaran Mahasiswa PGMI IAIN Metro - Nurul Afifah (AR-RIAYAH: Jurnal Pendidikan Dasar)
Learning Outcomes (CP) are defined as abilities acquired through internalizing knowledge of attitudes, skills, competencies, and accumulated work experience. Learning Outcomes (CP) is a measure of what someone gets in completing the learning process both structurally and unstructured. Determination of learning outcomes must refer to three references / documents; namely KKNI, SNPT and SNPG. Furthermore, the formulation of learning outcomes is described in the Graduate Standards of Competency (SKL) which are expressed in four elements, namely: Attitudes, general skills, knowledge and special skills.This study aims to determine the relevance of the PGMI curriculum to the achievements of IAIN Metro student learning. The qualitative research is a type of library research. Techniques for collecting data through documentation, interviews and observation. Furthermore, the collected data was analyzed by qualitative descriptive techniques.Learning Outcomes in the curriculum of the PGMI IAIN Metro department in accordance with the provisions of KKNI, SNPT and SNPG are as follows; The four elements of graduation standards that must be mastered by students of the PGMI IAIN Metro are elements of attitude that are internalized during the learning process, elements of general skills are the ability to become teachers in general, the element of knowledge is in-depth knowledge in education, psychology and teaching and special skills that is ; the ability of graduates of study programs according to the field of science / expertise in this case is as a class teacher in SD / MI.